Analisis Peran Media Sosial Instagram dalam Meningkatkan Awareness & Minat Beli Konsumen Secara Online (Studi Kasus Toko Topscore Sport) - Zeni Martin Firdaus; Muhammad Vano Budi Putra (Syntax Corporation Indonesia, 2023)
The rapid development of information and communication technology has led to a significant shift from conventional media to social media platforms. Social media, particularly Instagram, has gained widespread popularity in Indonesia as a means of communication, building social networks, sharing information, and conducting business. This study focuses on Topscore Sport, an Indonesian online shoe store that utilizes Instagram as a marketing tool to increase consumer purchase intention. By using Uses and Gratification Theory and the AIDA model, this research examines how Instagram contributes to the increasing consumer awareness and purchase intention. A qualitative research approach was employed, including interviews with four randomly selected students from Paramadina University. The findings highlight the importance of consistent product promotion on Instagram to build consumer awareness, and that Instagram plays a significant role in increasing consumer awareness and purchase intention which demonstrates the potential of Instagram social media platform as effective marketing tools for online businesses.